Eksistensi dan aktualisasi manusia sebagai al-insan ditinjau dari aspek psikologis - qohrunnada widodo, Aulia ainus safina (Maliki Interdisciplinary Journal, 2025)
This study discusses the self-actualization of humans as Al-Insan from a psychological perspective, identifying supporting and hindering factors in the process of self-actualization. The objective of this study is to understand the characteristics of self-actualizing individuals and the psychological factors influencing this process. The research method employed is literature study by analyzing various sources related to existential psychology, humanistic psychology, and the concept of Al-Insan in Islam. Findings indicate that self-awareness, intrinsic motivation, and social support are key supporting factors, while anxiety, fear, and internal conflict can hinder self-actualization. The study concludes that overcoming psychological barriers and utilizing spiritual and social support are essential for achieving self-actualization.